Development and Validation of Token Pedia: A Gamified Digital Mental Health Application for Adolescents in Islamic Boarding Schools - Nadila Kusuma Wardani; Ahmad Guntur Alfianto; Wira Daramatasia (Health and Technology Journal (HTechJ), 2026)
Adolescent mental health issues in Islamic boarding schools are escalating due to academic pressures, strict regulations, and pervasive stigmas. Conventional interventions remain insufficient, underscoring the need for accessible digital strategies. This study developed and evaluated "Token Pedia," a smartphone application integrating token economy psychotherapy, screening tools, psychoeducational modules, and gamification tailored for boarding school environments. A quantitative cross-sectional design was employed at an Islamic boarding school in Malang, Indonesia. Purposive sampling recruited 85 students aged 13–18 years. Participants completed a validated 20-item readability questionnaire assessing presentation, graphics, and integration. Content validity was analyzed using Aiken's V based on expert evaluations. User characteristics and readability metrics were evaluated using descriptive statistics and the Somers' D, Mann–Whitney, and Chi-square tests, with a significance level of p < 0.05. The application demonstrated exceptional readability among respondents. Linear regression analysis revealed no significant correlations between socio-demographic factors, including age, gender, length of stay, and psychiatric history, and application readability scores, indicating universal accessibility. Content validation utilizing Aiken’s V yielded high scores across all items, ranging from 0.826 to 0.915. These results classified the application as highly valid and culturally aligned with the target demographic. Token Pedia represents a valid, comprehensible, and culturally adaptive digital innovation. The application effectively enhances mental health literacy, mitigates social stigma, and fosters autonomous self-care and professional help-seeking behaviors among adolescents in religious educational settings.